Quantitative 3D Imaging of Trypanosoma cruzi-Infected Cells, Dormant Amastigotes, and T Cells in Intact Clarified Organs - Sánchez Valdéz, Fernando Javier (2021)
Reliable detection of Trypanosoma cruzi (T. cruzi) in vivo infections have long been needed to understand the complex biology of Chagas disease and to accurately evaluate the outcome of treatment regimens. Here, an integrated pipeline for automated quantification of T. cruzi-infected cells in 3D-reconstructed, cleared organs was developed. Light-sheet fluorescent microscopy allows us to accurately visualize and quantify not only actively proliferating but also dormant T. cruzi parasites and immune effector cells in whole-organs or tissues. Also, CUBIC-HistoVision pipeline to obtain uniform labeling of cleared organs with antibodies and nuclear stains was successfully adopted. Tissue clearing coupled to 3D immunostaining provides an unbiased approach to comprehensively evaluate drug treatment protocols, improve the understanding of the cellular organization of T. cruzi-infected tissues and is expected to advance discoveries related to anti-T. cruzi immune responses, tissue damage and repair in Chagas disease.